Perbedaan Kinerja Keuangan Bank Syari'ah dan Bank Konfensional - Lismiana, Lismiana; Abdullah, Mismiwati (Universitas muhammadiyah palembang, 2011)
The reserch problem in this study is whether there is a diference of financial peformance between islamic bank and conventional bank? The purpose of this study is to examine the differences of financial performance of islamic bank and conventional bank. This study is a comparative study wich compares the financial peformance of islamic bank and conventional bank from 2006 to 2009 Islamic bank samplesused in this studi is the bank muamalat indonesia,bank syari'ah mandiri, and bank syari'ah mega indonesia.Conventional bank samples used in this study is bank sentral asia, bank cimb niaga, bank danamon indonesia, bank internasional indonesia bank and bank permata. Secondary data is used an data collection tecnique is documentation independent sample t-test is employed. The result show that is a difference of CAR between islamic bank and conventional bank Meanwhile ROA, ROE,NPL,LDR and BOPO where found no difference. Overall there is a difference of financial peformace between islamic bank and conventional bank